PENGARUH VERBAL ABUSE TERHADAP KEPERCAYAAN DIRI MAHASISWA - Alphany Dyah Eka Putri; Annisa Frizki Maharani, Dhela Gusti Octavia, Ira Hoerun Nisa, Keyzia Zachwa Rachmadhina, Rijal Abdil (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to analyze the effect of verbal abuse on college students' self- confidence. Verbal violence, which is often overlooked, can have a significant impact on individuals' psychological development and their social interactions. The research method used was quantitative with descriptive and correlational survey design, involving 25 student respondents. The results of the analysis showed a significant negative relationship between verbal abuse and the level of self-confidence, where the higher the level of verbal abuse experienced, the lower the students' self-confidence. The findings underscore the importance of interventions and support in educational settings to increase students' self-confidence and prevent the negative impact of verbal abuse